Effectiveness of Grammar-Translation and Audio-Lingual Method in Learning English in Indonesian Universities - Yudhi Prasetyani, Nuning; Suhaimi, Suhaimi; Habibi, Habibi; Suhardianto, Suhardianto; Susrianingsih, Susrianingsih (International Journal of Language and Ubiquitous Learning, 2024)
Background. The Grammar-Translation Method (GT) and Audio-Lingual Method (ALM) are two main approaches to English language learning that have long been used in Indonesian university settings. GT emphasizes understanding grammatical structures and classical texts, while ALM focuses on repeated practice and the use of audio as a source of language input. Purpose. This study aims to evaluate the effectiveness of Grammar-Translation and Audio-Lingual Methods in English language learning in Indonesian universities, taking into account the views and experiences of lecturers and students. Method. Data were collected through an online survey asking respondents' opinions regarding the effectiveness of GT and ALM in English language learning. The survey included structured questions about respondents' perceptions of these learning methods. Results. Data analysis showed polarized opinions among respondents regarding the effectiveness of GT and ALM. Most respondents saw GT as effective in understanding language structures and classical texts, while ALM was considered effective in improving speaking and listening skills through repeated practice and audio. Conclusion. As a result of this study, it can be concluded that GT and ALM have their own advantages and disadvantages in English language learning in Indonesian universities. Therefore, a holistic and integrated approach that combines elements of both methods can be the most effective approach in preparing students for effective English communication in various contexts.